The regulation of microRNA in each of cancer stage from two different ethnicities as potential biomarker for breast cancer. (August 2021) - Ramanto, Kevin Nathanael; Widianto, Kresnodityo Jatiputro; Wibowo, Stefanus Satrio Hadi; Agustriawan, David
Abstract: miRNA has recently emerged as a potential biomarker for breast cancer. Even though many studies have identified ethnic variation affecting miRNA regulation, the effect of cancer stage within specific ethnicities on miRNA epigenetic remains unclear. The present study is designed to investigate miRNA regulation from two distinct ethnicities in specific cancer stages (non-Hispanic white and non-Hispanic black) using the TCGA dataset. Differentially expressed miRNAs were calculated by using the edgeR package. miRNAs with the highest or lowest log fold Change from each cancer stage were selected as a potential biomarker. miRNA-gene interaction was analyzed by using spearman correlation analysis, CLUEGO, and DIANA-mirpath. The association of biomarker candidates with diagnostic and prognostic performance was assessed using ROC and Kaplan-Meier survival analysis. miRNA-gene interaction analysis revealed the involvement of selected miRNAs in cancer progression. From eleven selected aberrant miRNAs, four of the miRNAs (hsa-mir-495, hsa-mir-592, hsa-mir-6501, and hsa-mir-937) are significantly detrimental to breast cancer diagnosis and prognosis. Hence, our result provides valuable information to explore miRNA's role in each cancer stage between non-Hispanic white and non-Hispanic black.